An experimental analysis of the Trombe wall temperature fluctuations for high range climate conditions: Influence of ventilation openings and shading devices - Briga-Sá, Ana (2019)
Submitted by Lanzinha (jcgl@ubi.pt) on 2019-01-21T17:25:41Z No. of bitstreams: 1 ENB Experimental analysis Trombe Wall.pdf: 3757075 bytes, checksum: 8cc105298b814ed3337474824bed4e2e (MD5)